2009
DOI: 10.17221/327-pse
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fungal communities in organically fertilized soil

Abstract: The research project was carried out as a field experiment with application of the following crop rotation system: industrial potato, spring barley for fodder, winter rape and winter wheat, established in the random distribution of blocks in triplicate on gleyic luvisol formed of silty light loam. The aim of the research was to determine the influence of diversified organic fertilization based on composted wastewater sediments and farm manure on the community of soil fungi as compared to fields without fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…The overall diversity of soil fungal communities decreased on amendment with chemical fertilizers (Allison et al, 2007;Beauregard et al, 2010;Kamaa et al, 2012). Like chemical fertilizers, the application of organic matter can also impact soil fungal communities, with their application frequently causing increased soil fungal diversity (Cwalina-Ambroziak and Bowszys, 2009;Kamaa et al, 2012;Song et al, 2015). These changes to soil fungal communities are associated with the alteration of soil nutrients and plant carbon inputs (Allison et al, 2007;Song et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall diversity of soil fungal communities decreased on amendment with chemical fertilizers (Allison et al, 2007;Beauregard et al, 2010;Kamaa et al, 2012). Like chemical fertilizers, the application of organic matter can also impact soil fungal communities, with their application frequently causing increased soil fungal diversity (Cwalina-Ambroziak and Bowszys, 2009;Kamaa et al, 2012;Song et al, 2015). These changes to soil fungal communities are associated with the alteration of soil nutrients and plant carbon inputs (Allison et al, 2007;Song et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the application of organic matter can suppress pathogenic fungal growth, and enhances the growth of fungi that antagonize these pathogenic species (Hoitink and Fahy, 1986;Gamliel and Stapleton, 1993;Bulluck et al, 2002;Zinati, 2005;Bo_ zena Cwalina-Ambroziak, 2009;Cwalina-Ambroziak et al, 2010;Mokhtar and El-Mougy, 2014;Saxena et al, 2015). For example, Cwalina-Ambroziak and Bowszys (2009) found that the aqueous extracts from compost inhibited mycelium growth in pathogens such as Botrytis cinerea, Colletotrichum coccodes, and those of the genus Fusarium.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were consistent with those of prior studies indicating that organic fertilizer addition increases bacterial community diversity (Chaudhry et al 2012, Jannoura et al 2013, Xiong et al 2017). Compared with conventional fertilization, organic fertilization had a stronger effect on soil fungal communities (Cwalina-Ambroziak and Bowszys 2009, Wei et al 2017). All treatments with bio-organic fertilizer increased soil fungal community diversity and richness.…”
Section: Discussionmentioning
confidence: 97%
“…Farmers tend to add excessive chemical fertilizers to increase soybean growth and production [9]. A continuous application of chemical fertilizers can affect the soil's microbiome by modifying the soil's chemical composition and physical character [10,11]. Moreover, only 30-50% of applied N fertilizer and 10-45% of P fertilizer are utilized by crops [12,13].…”
Section: Introductionmentioning
confidence: 99%